Development of antibodies against recombinant staphylococcal enterotoxin B from food poisoning cases - Hidayatun Nisa Purwanasari; Siti Isrina Oktavia Salasia; Fatkhanuddin Aziz; Madarina Wasissa; Fajar Budi Lestari; Christin Marganingsih Santosa (Veterinary World, 2024)
Background and Aim: Staphylococcal enterotoxin B (SEB) is the most common serotype involved in food poisoning. The aim of this study was to develop immunoassay detection methods using a recombinant enterotoxin B antigen protein to produce recombinant polyclonal antibodies in vivo.